Let's take bargaining models seriously: The decline in union power in Germany, 1992 - 2009 - Boris Hirsch; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2011)
Building on the right-to-manage model of collective bargaining, this paper tries to infer union power from the observed results in wage setting. It derives a time-varying indicator of union strength and confronts it with annual data for Germany. The results show that union power was relatively stable in the 1990s but fell substantially (by almost one-third) from 1999 to 2007. Two-thirds of this fall in union power follow from the reduction in the labour share relative to the capital share whereas changes in the gap between the net wage and the income when unemployed account for the remaining third. – – Dieser Beitrag versucht unter Verwendung des right-tomanage-Modells kollektiver Verhandlungen aus den beobachteten Lohnabschlüssen auf die entsprechende Gewerkschaftsmacht zurückzuschließen. Wir leiten einen zeitvarianten Indikator gewerkschaftlicher Stäarke her und berechnen ihn mit Jahresdaten für Deutschland. Die Ergebnisse deuten darauf hin, dass die Gewerkschaftsmacht in den 1990er Jahren relativ stabil war, aber von 1999 bis 2007 deutlich (um fast ein Drittel) zurückging. Zwei Drittel dieses Rückgangs der Gewerkschaftsmacht gehen auf eine Verringerung der Lohnquote relativ zur Kapitaleinkommensquote zurück, während Veränderungen im Abstand zwischen dem Nettolohn und dem Einkommen bei Arbeitslosigkeit für das restliche Drittel verantwortlich sind.
Keywords: J50; J51; 330; trade union power; wage bargaining; labour share; Germany; Tarifpolitik; Lohnverhandlungstheorie; Verhandlungsmacht; Gewerkschaft; Schätzung; Deutschland